Preparing the Community Based Education of Socio-Cultural Oriented for Children in the Industrial Revolution Era of 4.0 - Joni Indra Wandi; Nurhizrah Gistituati; Rusdinal (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This paper aimed to explore the preparation of community-based education of socio-cultural oriented for children in the Industrial Revolution Era of 4.0 as a new model in Pariaman City. This study reveals the importance of a positive correlation between education and the people's behavior to remain the socio-cultural norms. This model can be constructed through cooperative and collaborative education strategy based online learning. Preparation of this educational model built through cooperation with society as a stakeholder of education. This model allows the role of society and technology synergy gave birth to quality education without neglecting the social and local cultural values of the nation. Implementation of this idea can give the two sides to be achieved that is shaping the noble personality of the Indonesian children especially based cultured supreme divinity is one, civilized humanity and smart in technology to the advanced Indonesian community in the field of science and culture by nine steps are, character education, student-oriented learning system, teachers' learning skill improvement, collaborate with community organizations, social process-oriented education system, support from local government policy and community, build social and cultural coherence and set up diverse teaching materials from a variety of perspectives studies.